THE ROLE OF COGNITIVE PSYCHOTHERAPY IN STABILIZING MARITAL RELATIONSHIPS AND PROVIDING PSYCHOLOGICAL SERVICES TO COUPLES (World Bulletin of Education and Learning, 2026)
The article justifies and describes the role of cognitive psychotherapy in stabilizing marital relationships and providing them with psychological services.
Keywords: Marital relationships, healthy psychological environment in the family, scientifically based psychotherapies, cognitive psychotherapy.